Comparing organizational content and fan interaction on Twitter and Facebook in United States professional sport. Issue 5 (2nd September 2020) - Achen, Rebecca M.; Kaczorowski, John; Horsmann, Trisha; Ketzler, Alanda
ABSTRACT: Rationale/Purpose: The purpose of this study was to extend social media research by comparing how professional sport organizations in the United States used Facebook and Twitter in the off-season and how interaction on these networks differs. Design/Methodology/Approach: Data were collected from professional sport teams' Facebook and Twitter pages and deductive content analysis was used. Interaction data were then analyzed using multivariate multilevel modeling. Findings: Results suggested both networks were used most often for player and personnel promotion, and fans interacted most often with this content. However, Twitter was used more for information dissemination and Facebook was used more for organizational promotion. Overall, interaction on Facebook was significantly greater than interaction on Twitter. Practical Implications: Sport marketers and researchers can utilize these results to make strategic content plans to effectively engage fans. Research Contribution: This study used statistical modeling to compare and test differences between networks and focused on off-season content.